Transcending Cultural Frontiers - Zakaria, Norhayati; Abdul Talib, Asmat Nizam; Amelinckx, Andrea (Springer, 2020)
This book focuses on the cultural challenges often faced by international managers and global business operations. In the last few decades, the world has witnessed unprecedented economic turmoil, volatility, and uncertainty which has altered the political dynamics and sociocultural landscape around the globe and directly or indirectly affected international business activities. Further, new markets have opened up in every corner of the world. Brazil, Russia, India, and China, collectively known as BRIC, are strong emerging economic powers similar to the once captivated ‘Asian Tigers’ such as Hong Kong, Singapore, South Korea and Taiwan which rose decades ago. The emergence of these markets has heightened both the opportunities and challenges for national and international businesses. Multinational firms are gradually expanding in the emerging markets and are expected to become giants in the foreseeable future. As they expand, they also need to assume increasing social responsibilities in a global context, and it is important that the ways business is conducted are developed accordingly. As such, understanding the practices, challenges, and strategies that companies have developed is critical to global firm’s success. Against this background, the book highlights the importance of understanding cultural elements when managing multicultural human behaviors in the workplace. Based on conceptual and empirical work, it pushes the frontiers of knowledge of this emerging field in international business setup and management, and explores how globalization is changing the way in which multinational firms formulate their business strategies.